Lectotypifications of six taxa in Lycianthes (Solanaceae) - Costa-Silva, Rafael; Agra, Maria De Fátima (Phytotaxa, 2018)
Lycianthes comprises about 200 species, distributed mostly in the Neotropics but with 30 species in the Old World. It is a taxonomically complex group, and for more than a century its species were treated as part of Solanum. Together with Capsicum it constitutes the tribe Capsiceae. In this work six new lectotypes are designated for the following taxa of Lycianthes: L. acutangula (Griseb.) Bitter ssp. compressibaccata (Bitter) Bitter, L. cearaensis Bitter, L. coffeifolium Bitter, L. longidentata Bitter, L. ulei Bitter, and Solanum asarifolium Kunth & Bouché. Lycianthes cearaensis is shown to be distinct from L. pauciflora (Vahl) Bitter and Lycianthes amatilanensis (Coult. & Donn. Sm.) Bitter to be distinct from Lycianthes inaequilatera (Rusby) Bitter.